2017
DOI: 10.1017/s1431927617012727
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Elicits Stimulatory Action on the Adrenal Gland of Soay Ram: Morphometrical, Immunohistochemical, and Ultrastructural Study

Abstract: Endogenous melatonin is a hormone secreted by pineal gland; it has several roles in metabolism, reproduction, and remarkable antioxidant properties. Studies on the melatonin effect on the adrenal glands which are important endocrine organs, controlling essential physiological functions, are still deficient. In this study, we attempted to investigate the effect of exogenous melatonin treatment on the adrenal cortex and medulla using several approaches. Adrenal glands of 15 Soay ram were examined to detect the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
(60 reference statements)
1
7
0
Order By: Relevance
“…Our results revealed that melatonin administration increases the cross-sectional area of the nerve fibers. Similar findings were detected by Mokhtar, et al 26 and Hussein, et al 27 on the adrenal gland. Also, melatonin plays a key role in peripheral nerve regeneration and development of the nervous system via its antioxidant activity 43 Our results revealed that melatonin administration induces hypertrophy and hyperplasia on sebaceous glands.…”
Section: After Melatonin Treatmentsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results revealed that melatonin administration increases the cross-sectional area of the nerve fibers. Similar findings were detected by Mokhtar, et al 26 and Hussein, et al 27 on the adrenal gland. Also, melatonin plays a key role in peripheral nerve regeneration and development of the nervous system via its antioxidant activity 43 Our results revealed that melatonin administration induces hypertrophy and hyperplasia on sebaceous glands.…”
Section: After Melatonin Treatmentsupporting
confidence: 88%
“…According to 26 briefly, the rams of Soay breed (Ovis aries) were obtained from specialist breeders in Scotland. The skin of the scrotum of 15 adult Soay rams (aged 1.5 years) was used in this study.…”
Section: Materials and Methods Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The fixed samples were preprocessed for paraffin sectioning as described by Mokhtar et al (2017). Sections were deparaffinized in xylene and were hydrated in a descending series of ethanol concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…It was clear that the number of publications focused on TCs has shown an increasing yearly trend. They have been demonstrated in various tissues in different animal species, including the uterus and uterine tubes (Popescu et al, 2007), heart (Gherghiceanu & Popescu, 2012), vasculature (Zhou et al, 2010) urinary bladder (Zheng et al, 2012 b ), trachea (Rusu et al, 2012), meninges and choroid plexuses (Popescu et al, 2012), skin (Ceafalan et al, 2012), seminal vesicles (Abd-Elhafeez et al, 2017), adrenal gland (Mokhtar et al, 2017; Hussein et al, 2020), and efferent ductules (Abdel-Maksoud et al, 2019 a ).…”
Section: Introductionmentioning
confidence: 99%